Identification of flavonoids in Hymenaea martiana Hayne (Fabaceae) by HPLC-DAD-MSn analysis. Issue 14 (18th July 2021) - Pacheco, Alessandra Gomes Marques; Branco, Alexsandro; Câmara, Celso Amorim; Silva, Tânia Maria Sarmento; Silva, Telma Maria Guedes; de Oliveira, Ana Paula; Santos, Alan Diego da Conceição; Dutra, Lívia Macedo; Rolim, Larissa Araújo; de Oliveira, Gibson Gomes; Mendonça, Jacqueline Nakau; Lopes, Norberto Peporine; et al.
Abstract: Hymenaea martiana is a native tree known in Brazil as 'jatobá' and used in folk medicine to treat pain and inflammation. The aim of this work was to identify the flavonoids present in the crude ethanolic extract and ethyl acetate fraction using HPLC-DAD and LC-MS n analysis. The ethanolic extract was partitioned to obtain the ethyl acetate fraction. The analysis of astilbin content also was carried out by HPLC analysis. HPLC-DAD-ESI/MS n analysis of the ethanolic extract and ethyl acetate fraction revealed the presence of eleven peaks in the chromatograms, and all these peaks were identified: taxifolin, eucryphin, astilbin and 3 diastereoisomers, engeletin and 2 diastereoisomers, quercitrin and 2, 6, 3', 4'-tetrahydroxy-2-benzylcoumaran-3-one. The ethyl acetate fraction had a higher astilbin concentration (151.87 µg/mL) than the ethanolic extract (40.13 µg/mL). In conclusion, the species could be considered a good source of flavonoids, which can be related to the main chemotaxonomic markers for the genus Hymenaea . Graphical Abstract: